2007
DOI: 10.1148/radiol.2431060467
|View full text |Cite
|
Sign up to set email alerts
|

CT Screening for Lung Cancer: Diagnoses Resulting from the New York Early Lung Cancer Action Project

Abstract: The NY-ELCAP regimen of screening revealed that annual CT screening for lung cancer resulted in identification of a high proportion of patients with early-stage disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(14 citation statements)
references
References 23 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Due to the substantial survival advantage to early detection, there have been extensive efforts to detect lung cancer at an early stage. The Early Lung Cancer Action Project (ELCAP) [5] and the National Lung Cancer Screening Trial (NLST) [4] are prospective studies that screened symptom-free high-risk smokers using low dose computed tomography (CT) and preliminary results show increased ability to detect early stage, potentially curable lesions [3]. The NLST was stopped early in November of 2010 after the preliminary data revealed a 20.3% decrease in lung cancer deaths in the CT screening arm of the trial [4], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the substantial survival advantage to early detection, there have been extensive efforts to detect lung cancer at an early stage. The Early Lung Cancer Action Project (ELCAP) [5] and the National Lung Cancer Screening Trial (NLST) [4] are prospective studies that screened symptom-free high-risk smokers using low dose computed tomography (CT) and preliminary results show increased ability to detect early stage, potentially curable lesions [3]. The NLST was stopped early in November of 2010 after the preliminary data revealed a 20.3% decrease in lung cancer deaths in the CT screening arm of the trial [4], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Costs included all follow-up from suspicious nodules identified in screening; in the first year of screening, 21% of participants required follow-up LDCT scan or biopsy for a positive result (nodules larger than five millimeters in diameter) and in subsequent years, positive results from screening dropped to 7% (see Exhibit 1 and the Appendix in [7] for detailed decision trees). These values were based on the New York ELCAP [30] and personal communication with the ELCAP lead investigator (Claudia Henschke, December 6, 2010). They are slightly higher than those reported in the New York ELCAP (14% at baseline and 6% at follow-up) [30] and I-ELCAP studies (16% at baseline) [31] and slightly lower than the 27% at baseline reported by the NLST, though NLST defined a positive result as greater than four, rather than five, millimeters in diameter [10].…”
Section: Methodsmentioning
confidence: 99%
“…We compared the SF-36v2 data from the lung cancer survivor sample to a cohort of current smokers and former smokers who had completed the SF-12v2 at the time of enrollment in a large, low dose helical computer tomography (CT scan) lung screening trial conducted in the New York metropolitan region [16] equivalent to the geographic catchment area of the comprehensive cancer center treating the lung cancer survivors. We chose this novel comparison group because these individuals were similar to our survivor population in terms of demographic characteristics (older) and smoking history, except for not having been diagnosed and treated for NSCLC.…”
Section: Methodsmentioning
confidence: 99%
“…We examined demographic, medical, and psychological correlates of HQOL. In contrast to other cross-sectional studies that compared HQOL to the general population, we compared HQOL (SF-36v2) scores from lung cancer survivors with a comparison sample of older adults who had enrolled in a lung screening trial [16] and who had screened negative for lung cancer. Use of this matched comparison sample allowed us to better control for demographic, tobacco-related, and comorbidity variables that can influence interpretation of HQOL outcomes.…”
Section: Introductionmentioning
confidence: 99%